2013
DOI: 10.4067/s0717-97072013000400019
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Au/Ag Metal Superstructures From Macromolecular Metal Complexes in Solid-State

Abstract: Novel bimetallic Au/Ag superstructures have been prepared from solid-state pyrolysis of the macromolecular complexes Chitosan(MLn/M'Ln) n y PSP-4-PVP×( MLn/M'Ln)n with MLn = AuCl 3 and M'Ln = Ag(CF 3 SO 3 ).The characterization was made from XRD (X-ray diffraction of powder), SEM and EDS analysis. Morphologies are influenced by both the nature of the polymer and the metal/polymer, molar ratio of the polymer precursor. EDS analysis suggests a core/shell Au/Ag structure for the materials. A probable mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…In a typical synthesis [7], the respective metallic salts AuCl 3 and Ag(CF 3 SO 3 ) were added in a Schlenk tube using CH 2 Cl 2 as solvent under magnetic stirring and then the respective Chitosan amount was added according to the 1:1 (1) or 1:5 (2) molar ratio.…”
Section: 1-precursors Synthesis: Chitosan•(mln/m'ln)nmentioning
confidence: 99%
See 2 more Smart Citations
“…In a typical synthesis [7], the respective metallic salts AuCl 3 and Ag(CF 3 SO 3 ) were added in a Schlenk tube using CH 2 Cl 2 as solvent under magnetic stirring and then the respective Chitosan amount was added according to the 1:1 (1) or 1:5 (2) molar ratio.…”
Section: 1-precursors Synthesis: Chitosan•(mln/m'ln)nmentioning
confidence: 99%
“…In a typical synthesis [7] the respective metallic salts AuCl 3 and Ag(CF 3 SO 3 ) were added in a Schlenk tube using CH 2 Cl 2 as solvent under magnetic stirring and then the respective Poly(styrene-co-4-vinylpyridine) amount was added according to the 1:1 (3) or 1:5 (4) molar ratio. After about 6 days the supernatant solution (provided the solid decanted) was extracted with a syringe and the solid dried under reduced pressure to give a solid with diverse colors.…”
Section: Precursors Synthesis: Psp-4-pvp•(mln/m'ln)nmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology of bimetallic complexes in the presence of polymers depends on various factors. For example, it was shown that the morphology of "foamy" complexes with chitosan and polystyrene block (4-vinylpyridine)] PSP-4-PVP in the presence of Au/Ag depends on both the nature of the polymer and the molar ratio of the polymer / metal salt [20][21][22]. Polymer PSP-4-PVP in a 1:1 ratio form the most porous morphologies.…”
Section: Introductionmentioning
confidence: 99%
“…The application of nanostructured materials to electronic solidsate devices or to high temperature technology requires, however, adequate solid-state methods for obtaining nanostructured materials [15][16][17][18][19][20]. Recent studies reported that the evaporation of solvent to obtain Au nanoparticles in solid-state, for an adequate incorporation to a solid-state device -for instance-, results in 3D Au superstructures with properties different to those of Au nanostructures [21][22][23][24]. Then, the development of new solid state methods to prepare metallic nanostructured materials is a constant challenge.…”
Section: Introductionmentioning
confidence: 99%